1990
DOI: 10.1080/01932699008943285
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Alkanes on the Formation of Ultrafine Silver Bromide Particles in Ionic W/O Microemulsions

Abstract: Ultrafine Ag8r particles formed in wlo microemulsions with different chain iength of aikanes were studied by UV-VIS spectrophotometry, stopped-fiow spectrophotometry and transmission electron microscopy.The ultraflne particies of Ag8r (5-7 nm in diameter) were obtained by mixing two separately prepared microemuision systems both containing AOT, n-hexane and an aqueous soiution of either AgN0 3 or Na8r. The size distribution of the near-Ly sphericai Ag8r particles broadened from S to about 10 nm as chain length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…On the other hand, a substantially fluid interface in the microemulsion enhances the rate of precipitation. Thus, by controlling the structure of the interface, one can change the reaction kinetics in microemulsions by an order of magnitude [57]. It has been further shown that the structure of oil, alcohol and ionic strength of the aqueous phase can significantly influence the rigidity of the interface and the reaction kinetics [28,57].…”
Section: Reactions In Microemulsionsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, a substantially fluid interface in the microemulsion enhances the rate of precipitation. Thus, by controlling the structure of the interface, one can change the reaction kinetics in microemulsions by an order of magnitude [57]. It has been further shown that the structure of oil, alcohol and ionic strength of the aqueous phase can significantly influence the rigidity of the interface and the reaction kinetics [28,57].…”
Section: Reactions In Microemulsionsmentioning
confidence: 99%
“…We have shown that the interfacial rigidity of droplets in microemulsions can be controlled by the structure of the oil, surfactant or cosurfactant [28,57]. A high interfacial rigidity leads to a low inter-droplet attraction and low rate of precipitation, while a fluid interface leads to a higher rate of precipitation.…”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bandyopadhyaya et al (Bandyopadhyaya et al, 1997) (Chew et al, 1990) have studied the effect of alkanes in the formation of AgBr particles in ionic W/O microemulsions (using AOT as surfactant), where the transmittance of the reactions were followed with time with UV-Vis and Stopped-Flow Spectrophotometry. They have found an increase on reaction rate with the chain lenght of the alkane.…”
Section: Reaction Kineticsmentioning
confidence: 99%